The Impact of Videos Based Discovery Learning Towards Young Learners’ Speaking Skill During Pandemic Covid-19 - Pirdayanti, Ni Putu Ayu; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu; Adnyayanti, Ni Luh Putu Era (Universitas Pendidikan Ganesha, 2022)
Speaking skill is one of the crucial language skill needed in communication. However English teachers feel difficult in teaching speaking skill through online learning during this pandemic situation. English teachers need to use innovative teaching media to attract students’ attention and develop students’ speaking skill. The study purposed to investigate the impact of videos-based discovery learning towards young learners’ speaking skill in pandemic Covid-19. The study included a single intact class which divided into 30 students of fourth graders. The instrument was speaking test and the treatments instrument. The study employed quantitative study with one group pretest-posttest design. The data collection was analyzed descriptively and inferentially which aided by IBM SPSS Statistics 24. The effect size was measured by Effect Size Calculator. The findings show that the group posttest mean was higher than the pretest mean while the significant value of Sig. (2-tailed) was .000 which was lower than Sig. value of .05. The effect size was (1.94) which can be stated as large effect. Conclusively, there is a positive significant impact of videos-based discovery learning towards young learners’ speaking skill in pandemic Covid-19.